3-(Benzo[d][1, 3]dioxol-5-ylamino)-N-(4-fluorophenyl)thiophene-2-carboxamide overcomes cancer chemoresistance via inhibition of angiogenesis and P-glycoprotein efflux pump activity12. Issue 14 (11th March 2015) - Mudududdla, Ramesh; Guru, Santosh K.; Wani, Abubakar; Sharma, Sadhana; Joshi, Prashant; Vishwakarma, Ram A.; Kumar, Ajay; Bhushan, Shashi; Bharate, Sandip B.
Abstract : Thiophene-2-carboxamides displayed dual inhibition of angiogenesis and P-gp efflux pumps. Abstract : 3-((Quinolin-4-yl)methylamino)- N -(4-(trifluoromethoxy)phenyl)thiophene-2-carboxamide (OSI-930, 1 ) is a potent inhibitor of c-kit and VEGFR2, currently under phase I clinical trials in patients with advanced solid tumors. In order to understand the structure–activity relationship, a series of 3-arylamino N -aryl thiophene 2-carboxamides were synthesized by modifications at both quinoline and amide domains of the OSI-930 scaffold. All the synthesized compounds were screened for in vitro cytotoxicity in a panel of cancer cell lines and for VEGFR1 and VEGFR2 inhibition. Thiophene 2-carboxamides substituted with benzo[ d ][1, 3]dioxol-5-yl and 2, 3-dihydrobenzo[ b ][1, 4]dioxin-6-yl groups1l and1m displayed inhibition of VEGFR1 with IC50 values of 2.5 and 1.9 μM, respectively. Compounds1l and1m also inhibited the VEGF-induced HUVEC cell migration, indicating its anti-angiogenic activity. OSI-930 along with compounds1l and1m showed inhibition of P-gp efflux pumps (MDR1, ABCB1) with EC50 values in the range of 35–74 μM. The combination of these compounds with doxorubicin led to significant enhancement of the anticancer activity of doxorubicin in human colorectal carcinoma LS180 cells, which was evident from the improved IC50 of doxorubicin, the increased activity of caspase-3 and the significant reduction in colony formation ability of LS180 cells after treatment with doxorubicin. Compound1l showed a 13.8-fold improvement in the IC50 of doxorubicin in LS180 cells. The ability of these compounds to display dual inhibition of VEGFR and P-gp efflux pumps demonstrates the promise of this scaffold for its development as multi-drug resistance-reversal agents.